A Neglected Unusual Galeazi Fracture Dislocation In 12 Years Child: Management (Community Based Medical Journal, 2015)
A galeazi fracture is defined as a fracture of the shaft of the radius with dislocation of the distal radioulnar joint (DRUJ). Isolated radial shaft fractures with or without DRUJ dislocation in children are unusual in clinical practice. If there is fracture the degree of angulation is measured and accordingly managed. A 12 years boy came to the casualty department of Community Based Medical College Hospital Bangladesh (CBMCH,B) with the history of fall from bicycle on out stretcher right hand 5 years back, diagnosed to have fracture shaft of right radius. X-ray examination revealed old fracture at the junction of the middle and lower third of right radial shaft with feature of nonunion with volar angulation 30° (180-1500) and interosseous angulation 150 (180-165°). Patients was operated by open reduction and internal fixation (ORIF) of the fracture using dynamic compression plate (DCP) and screws and we corrected the angulation to near normal status and also correction of DRUJ done to its near normal anatomy. Postoperatively wound healed well and patient achieved full range of motion by three weeks. Radiologically the fixation was satisfactory and at the 6 weeks fracture was united. In conclusion, an old unusual galeazzi fracture dislocation in a child below 14 years with volar / dorsal / interosseus angulation more than 150 and rotational angulation more than 30° must be managed surgically to get near normal anatomy of bone as well as near normal range of motion.CBMJ 2015 January: Vol. 04 No. 01 P: 41-44